The Impact of COVID-19 in Brazil Through an Educational Neuroscience Lens: A Preliminary Study - Camila G. Fonseca; Camila L. L. Dias; Marcus L. L. Barbosa; Maria Julia Hermida; Luiz Renato R. Carreiro; Alessandra G. Seabra (Brain Sciences)
Background: Educational neuroscience has made important contributions to show how the COVID-19 pandemic impacted schooling. In countries like Brazil, with significant educational inequality, the suspension of in-person classes worsened these disparities, as low-income families faced difficulties accessing remote learning. Methods: This study evaluated executive functions (EF) and academic skills in reading, writing, and maths for 178 public school students from the first to ninth grades in São Paulo, Brazil, comparing them with pre-pandemic norms to assess possible differences. EF were assessed using the Hayling Test, Digit Span Task, and Verbal Fluency, while academic skills were measured by the School Performance Test II. To analyse differences between the sample of this study and the pre-pandemic normative samples, one-sample t-tests were performed. Due to the small sample size, segmented by school grade and age, the bootstrapping resampling method was used, and the effect size was measured with Cohen’s d. Results: A one-sample t-test showed significant differences between times, with lower post-pandemic performance in verbal fluency (9–14 years old), working memory (10–14 years old), and inhibitory control across all age groups. Writing skills were lower from the fifth to eighth grades and reading from the fourth to eight grades. Maths skills were lower in the fourth, eighth, and ninth grades. Better post-pandemic performance was seen in working memory (6 and 7 years old). Conclusions: Students in the upper grades of elementary school during the pandemic were most impacted by the suspension of in-person teaching, highlighting the importance of schooling and the need for recovery efforts at these levels.